Efficacy of ileostomy in Crohn's disease of the large intestine with perianal involvement - Yu. A. Shelygin; V. N. Kashnikov; K. V. Bolikhov; A. V. Vardanyan; I. L. Khalif (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To estimate efficacy of ileostomy in patients with Crohn's disease of the large intestine with perianal involvement.Material and methods. Overall 43 patients with Crohn's disease of the large intestine with perianal involvement who underwent ileostomy in January, 1998 to July, 2009 in The State scientific center of coloproctology were included in original study. According to the spread of inflammatory process patients were distributed as follows: in 4 patients (9,3%) – proctosigmoiditis, in 15 (34,8%) – left-side lesion and in 24 (55,9%) – total involvement of the large intestine. Perianal lesions were presented by following types: ulcers-anal fissures – in 6 (14%) patients, rectal fistulas – in 12 (27,9%), strictures of anal canal – in 3 (6,9%), combinations of two and three types of perianal lesions were present in 22 (51,2%) patients. Results. Thirty five of 43 patients (81,3%) were monitored in terms from 1 to 12 months (М=5,5±2,6). Twenty four of 35 (68,5%) patients underwent local conservative treatment in period from 1 to 6 months (М=4,1±1,1), that provided healing in 11 cases to 2,8±1,4 month. Surgical treatment of perianal lesions was performed in 11 (31,5%) patients in terms from 2 to 12 months (М=5,9±3,6), healing was obtained in 9 patients on average up to 4,5±2,2 month in terms from 2 to 9 months.Conclusion. At total involvement of the large intestine in combination to two and more types of the perianal lesions along with severe metabolic disorders, ileostomy should be applied as the first-line surgical treatment.